ANALISIS PENDEKATAN EXPERIENTIAL MARKETING (Studi Kasus : Benyalin Central Simpang Dua Kabupaten Ketapang) - B11107058, Aloysius Eriswan (Jurnal Manajemen Update, 2013)
Marketing is one of the keys of success of a particular business. Without agood strategy businesses can not survive and thrive in the midst of a very tightcompetition. Marketing as well as a work of art created by an artist, who has acreative and innovative works and integrates with the situation then he is the winner.So it is with the business of the restaurant Benyalin Central are trying to create anunforgettable experience for consumers with an approach consisting of ExperientialMarketing Sense, Feel, Think, Act, and Relate. The purpose of this study was toanalyze the effect of each - each variable sense, feel, think, act and relate toexperiential marketing.In this study, data were collected through purposive sampling method todistribute questionnaires to 100 respondents customer. Then the analysis of the dataobtained by using SPSS 16.0. Data that meets the test of validity, reliability testing,and test the assumptions of classical processed to generate a regression equation asfollows:Y = ( -0,140) + 0,039X1 + 0,057X2 + 0,096X3 + 0,162X4 + 0,644X5Hypothesis testing using t-test showed that the five independent variablesunder study has a positive on the dependent variable. With the most dominantvariable is the variable affecting relate. Then through the F test can be seen that thefive significant variables together to experiential marketing. Figures obtainedAdjusted R square of 0.856 indicates that 85.6% Experiential Marketing can beexplained by the five independent variables used in the regression equation. The restis explained by other variables such as customer loyalty.